2019
DOI: 10.34198/ejcs.2219.271291
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of 1,1-Diamino-2,2-Dinitroethylene and Gallium - DFT Treatment

Abstract: 1,1-diamino-2,2-dinitroethylene, commonly known as FOX-7, is an insensitive pull-push type explosive of nitramine class. Aluminized FOX-7, depending on its Al content and multiplicity was found to be susceptible to decomposition. Gallium atom, a third group element below Al, also has an open shell electronic configuration. The present study considers FOX-7+nGa composites (n:1-3) and within the constraints of density functional theory at the level of UB3LYP/6-311++G(d,p) it has been found that gallium atom does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…For energies of isomeric structures B3LYP functional bias in favor of one type of spin states of isomeric structures [37][38][39][40]. In the case of some aluminized explosives lower spin state is favored (UB3LYP/6-311++G(d,p)) [41][42][43]. Therefore, TNAZ +2Al composite could have some excitation at the IR region.…”
Section: Resultsmentioning
confidence: 99%
“…For energies of isomeric structures B3LYP functional bias in favor of one type of spin states of isomeric structures [37][38][39][40]. In the case of some aluminized explosives lower spin state is favored (UB3LYP/6-311++G(d,p)) [41][42][43]. Therefore, TNAZ +2Al composite could have some excitation at the IR region.…”
Section: Resultsmentioning
confidence: 99%
“…Gallium may produce Ga 2 O and Ga 2 O 3 which yield heat energy of 340 and 1079 kJ/mol, respectively [49]. The interaction of gallium alone with FOX-7 has been published [50]. It has been found that gallium atom does not initiate any bond rupture.…”
Section: Resultsmentioning
confidence: 99%
“…Kretschmer et al investigated the chemical stability, sensitivity and mechanical and explosive properties of mixtures of FOX-7 with paraffin, ethylene-propylene rubber (EPM) and the polyacrylate elastomer (Hy Temp) [18]. Interactions of FOX-7 with various elements are found in the literature [19][20][21].…”
Section: Introductionmentioning
confidence: 99%